Zn-doped NiO Thin Films Deposited by Spray Pyrolysis Technique Using Solar Dish - غريسي, علوي محمد سليم; عقيل, جغبالة; بدر الدين, ساكر; عبد الستار, برتيمة (University of El-Oued, 2022)
"In recent years, significant studies have been conducted on transparent semiconducting oxide thin films. Due to their promising optical characteristics, high stability, and good electrical properties, n- or p-type semiconducting metal oxides are known as transparent conducting oxides . Among the various P-type semiconductors, nickel oxide is one with a direct band gap that varies between 3.6 and 4 eV depending on the deposition technique, and has attracted much attention due to its important applications in optoelectronic devices such as ultraviolet optoelectronic devices, energy efficient smart windows, positive electrodes in batteries, solar thermal absorbers, fuel cells, catalysts, in materials for gas or temperature sensors, such as CO sensor, H2 sensor, and formaldehyde sensors, in electrochromic display devices, and so on. In this work, NiO will be deposited with various Zn-doping percentages (0, 1, 5, 10%), at a deposition temperature of 350 ֯C, according to the spray pyrolysis technique and with the use of solar energy as substrate heater. Structural, optical and electrical characterization will be achieved. Those properties will be examined using X-ray diffraction (XRD) to investigate structural properties such as the crystalline quality and nature of the layers, grain size, dislocation density, and strain. UV-visible spectrophotometer will be used to analyse the optical characteristics such as the spectrum of the transmittance and the optical gap energy whereas the four probes method will be used to measure the electrical conductivity of the prepared samples. ""في السنوات الأخيرة ، أجريت دراسات مهمة على أغشية رقيقة شفافة من أكسيد أشباه الموصلات. نظرًا لخصائصها البصرية الواعدة ، واستقرارها العالي ، وخصائصها الكهربائية الجيدة ، تُعرف أكاسيد الفلزات شبه الموصلة من النوع n أو p باسم أكاسيد التوصيل الشفافة . من بين أشباه الموصلات من النوع P ، يعتبر أكسيد النيكل واحدًا به فجوة نطاق مباشرة تتراوح بين 3.6 و 4 فولت اعتمادًا على تقنية الترسيب ، وقد جذب الكثير من الاهتمام نظرًا لتطبيقاته المهمة في الأجهزة الإلكترونية الضوئية مثل الأشعة فوق البنفسجية الإلكترونية الضوئية الأجهزة ، والنوافذ الذكية الموفرة للطاقة ، والأقطاب الكهربائية الموجبة في البطاريات ، والممتصات الحرارية الشمسية ، وخلايا الوقود ، والمحفزات ، في المواد الخاصة بأجهزة استشعار الغاز أو درجة الحرارة ، مثل مستشعر ثاني أكسيد الكربون ، ومستشعر H2 ، ومستشعرات الفورمالديهايد ، في أجهزة العرض الكهروضوئية ، و قريباً. في هذا العمل ، سيتم ترسيب NiO بنسب مختلفة من منشطات الزنك (0 ، 1 ، 5 ، 10٪) ، عند درجة حرارة ترسيب 350 درجة مئوية ، وفقًا لتقنية الانحلال الحراري بالرش وباستخدام الطاقة الشمسية كمسخن ركيزة. سيتم تحقيق الخصائص الهيكلية والبصرية والكهربائية. سيتم فحص هذه الخصائص باستخدام حيود الأشعة السينية (XRD) للتحقق من الخصائص الهيكلية مثل الجودة البلورية وطبيعة الطبقات وحجم الحبيبات وكثافة الخلع والانفعال. سيتم استخدام مقياس الطيف الضوئي المرئي بالأشعة فوق البنفسجية لتحليل الخصائص الضوئية مثل طيف النفاذية وطاقة الفجوة الضوئية بينما سيتم استخدام طريقة المجسات الأربعة لقياس التوصيل الكهربائي للعينات المعدة. "
مذكرات ماستر تخصص طاقات متجددة
Keywords: transparent semiconducting oxide, P-type semiconductors, NiO, Zn-doping, spray pyrolysis technique, solar energy.; أكسيد أشباه الموصلات الشفاف، أشباه الموصلات من النوع P، أكسيد النيكل، منشطات الزنك، تقنية الانحلال الحراري بالرش، الطاقة الشمسية.